Language Development and the Ontogeny of the Dorsal Pathway - Friederici, Angela D. (Frontiers in Evolutionary Neuroscience, 2012)
In the absence of clear phylogenetic data on the neurobiological basis of the evolution of language, comparative studies across species and across ontogenetic stages within humans may inform us about the possible neural prerequisites of language. In the adult human brain, language-relevant regions located in the frontal and temporal cortex are connected via different fiber tracts: ventral and dorsal pathways. Ontogenetically, it has been shown that newborns display an adult-like ventral pathway at birth. The dorsal pathway, however, seems to display two subparts which mature at different rates: one part, connecting the temporal cortex to the premotor cortex, is present at birth, whereas the other part, connecting the temporal cortex to Broca’s area, develops much later and is still not fully matured at the age of seven. At this age, typically developing children still have problems in processing syntactically complex sentences. We therefore suggest that the mastery of complex syntax, which is at the core of human language, crucially depends on the full maturation of the fiber connection between the temporal cortex and Broca’s area.